Can AI Predict Stroke Risk from Clinical Data? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2020)
Stroke remains a leading cause of mortality and long-term disability worldwide, making its prevention a critical public health priority. For decades, clinici...
Keywords: AI in Neurology; Predict; Stroke; Clinical; Artificial Intelligence; Machine Learning; Deep Learning